1972
DOI: 10.1161/01.cir.46.5.856
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of Electromechanical Systole as a Manifestation of Excessive Adrenergic Stimulation in Acute Myocardial Infarction

Abstract: SUMMARYThe relationship between shortened electromechanical systole (QS2I) and 24-hour urinary catecholamine excretion (E + NE) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
5

Year Published

1977
1977
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 32 publications
2
16
0
5
Order By: Relevance
“…In the present study an excessive adrenergic tone was found the day before CBS as manifested by an increase in the urinary catecholamine excretion and a short QS2I (24,26). In the propranolol group the QSzI was within normal range indicating good beta blockade (5,6).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the present study an excessive adrenergic tone was found the day before CBS as manifested by an increase in the urinary catecholamine excretion and a short QS2I (24,26). In the propranolol group the QSzI was within normal range indicating good beta blockade (5,6).…”
Section: Discussionsupporting
confidence: 54%
“…The PEPIL VET was not different in both groups before and two weeks after surgery, and was mildly but significantly increased. Patients with peri operative infarction were exluded from this analysis, since it is known that peri-operative infarction produces a significant deterioration in left ventricular performance (4,8,10,20,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…34 This is relevant to the previous demonstration that not only heart rate but also changes in myocardial inotropism 35 and increase of catecholamines release 33 can produce changes in diastolic time/left-ventricular ejection time ratio. All these factors tend to occur at high altitude; an activation of the sympathetic system leads to increased myocardial inotropism, and this is associated with prolongation of the left-ventricular systolic period and with the corresponding relative reduction in duration of diastole 9 associated with changes in central pulse waveform.…”
Section: Subendocardial Viability Ratiomentioning
confidence: 59%
“…Conversely, a significant difference was found between the two examined groups in the effects of dynamic exercise upon HR, systolic arterial pressure, electromechanical systole and consequently, on diastolic time, suggesting a different cardiovascular re sponse to stress. In fact, CAD patients showed a greater exercise-induced increase in HR and SBP, probably related to a more adrenergic stimulation [13][14][15][16], and a smaller decrease in electromechanical sys tole, resulting in a more marked shortening of %D. In the two examined groups at rest, no difference was found in the slopes and intercepts of the obtained linear regressions between Q-inc and HR as well as between %D and RR, suggesting that in the resting condition in CAD patients, the physiological ratio between systole and diastole is well preserved.…”
Section: Discussionmentioning
confidence: 99%